Transmission of Coxiella burnetii to Calves from Infected Cows - Radinović, Miodrag; Davidov, Ivana; Kovačević, Zorana; Erdeljan, Mihajlo; Pajić, Marija; Galfi, Annamaria (Acta Scientiae Veterinariae, 2019)
Background:Coxiella burnetii is the causative agent of a very important disease with zoonotic potential. Infected cows represent risk for spreading of infection to humans and to other animals on farm and also to their offspring. There is possibility for calves from infected cows to be infected nearly after parturition or during intrauterine life. Studies have shown that Coxiella burnetii initially infects the placenta and subsequent spread to the fetus may occur either by haematogenous or by the amniotic-oral route providing congenital infection. The main objective of the present study is to determine the presence of Coxiella burnetii genome in milk serum of infected cows and blood serum of calves. Materials, Methods & Results: A total of 200 blood serums from dairy cows were tested for presence of antibodies to Coxiella burnetii and nine of those were found positive. These animals compiled experimental group. From animals in experimental group milk samples during lactation, pregnancy and the postpartum period were collected. Samples were used for performing PCR test for determination of Coxiella burnetii presence in milk serum. On calving of each cow blood samples were taken from calves during first 24 hours after calving, from jugular vein. These blood samples were also used for PCR test to determine the presence of Coxiella burnetii. Milk serum analysis showed presence of Coxiella burnetii genome in serum, indicating on intermittent excretion. During lactation, the excretion of bacteria was greatest in the second stage when 80% of milk serum samples were positive for Coxiella burnetii. In the colostrums stage, there was a high percentage of Coxiella burnetii excretion through milk (50% of positive milk serum samples). The lowest percentage of excretion through milk was in the first stage of lactation. Analyzing blood serum samples from calves, taken on first day at calving using PCR method, all serums were positive for presence of Coxiella burnetii genome. Discussion:In animals, Coxiella burnetii is found in the reproductive system, both uterus and mammary glands, and may cause abortion or infertility. The high prevalence of Coxiella burnetii infection in dairy cattle with reproductive problems showed that these infected cattle play an important role in maintaining the infection and in disseminating of pathogenic agent to environment. The lowest percentage of excretion of Coxiella burnetii was in the first stage of lactation, amounting to 16.6%. With the transition to the next stage of lactation, a striking increase in the percentage of excretion was noticed. In the second stage it was 80%. In the third stage there was decrease to 40.6%. In colostrums stage percentage of excretion through milk was 50%. Similar results claims that excretion of Coxiella burnetii through milk starts after eight to twelve weeks of lactation in most cows. This period coincides with second stage of lactation as we divide it. Blood serums taken from calves were proven positive on Coxiella burnetii which indicates on intrauterine infection as described in the literature. Intrauterine infection takes place after placenta infection when bacteria penetrate the placenta and contaminate the amniotic fluid and gets aspirated or swallowed by fetus. Besides this,haematogenous spread can also occur.